PENGARUH IMPOR KOPI LIBERIKA MERANTI OLEH MALAYSIA TERHADAP PERTUMBUHAN EKONOMI MASYARAKAT DESA KEDABU RAPAT TAHUN 2018-2020 - Dwi Akhmeilia; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research analyzes how the influence of imports of Liberika Meranti coffee commodities by Malaysia and Kedabu Rapat Village with a highdemand rate. This collaboration can provide changes to the economy of the coffee producing factory along with all local communities who are involved in the Liberika Meranti coffee proccesing in Kedabu Rapat Village, as with factory workers, as well as local farmers on a small scale.This research method applies a qualitative method with data collection techniques in the form of triangulation, in which the data collection will be combined into several techniques such as library research, observation, and interview techniques. The perspective of this research uses the perspective of Liberalism by using the theory of Absolut Advantage from Adam Smith.This research shows that the people of Kedabu Rapat who are involved in the Liberika Meranti coffee processing have additional income, so as they are able to change the economic situation through Malaysia's regular demand of around 4-6 tons/month. With the number of requests, the factory opens job vacancies up to 300 people. They find wages according to work placements ranging from IDR 100,000, - IDR 2,000,000 for workers, and IDR 7,000,000/month for local coffee farmers.Keywords: Export-Import Coffee, Economic Growth, Kedabu Rapat Farmers.